Wetting and drying: reducing greenhouse gas emissions and saving water from rice production - Searchinger, Tim; Adhya, T.K.; Linquist, Bruce; Wassmann, Reiner; Yan X (2014)
A sustainable food future will require reductions in greenhouse gas emissions from agriculture even as the world produces substantially more food. The production of rice, the staple crop for the majority of the world’s population, emits large quantities of methane, a potent greenhouse gas. According to various governments, global rice production emits 500 million tons of greenhouse gases (carbon dioxide equivalent) per year—or at least 10 percent of total agricultural emissions. The figure may be closer to 800 million tons when adjusted for new estimates by the Intergovernmental Panel on Climate Change of the sustained warming effect of methane. Although uncertain, there is evidence that increasing levels of carbon dioxide in the atmosphere could also increase future rice-related emissions substantially through its effect on soil microbes.